Rủi ro khí hậu và chính sách cổ tức: Bằng chứng từ các quốc gia châu Á - Tran Thi Hai, Ly; Dinh Thi Thu, Hong; Nguyen Huu, Tuan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
Climate change is becoming increasingly evident and has far-reaching impacts on economic and social aspects. This study examines the impact of climate risk on corporate dividend policies. Using data from 23 Asian countries over the period 2010-2022, the study finds that climate risk leads to lower corporate dividend payments. This result is consistent across multiple robustness tests. The study also examines how financial development mitigates the impact of climate risk on dividend policy. The findings provide valuable insights for investors to evaluate corporate dividend policies and improve the understanding of the reasons behind the managers’ dividend policy choices when companies face climate change risks.